Efektivitas Permainan Bowling Adaptif Terhadap Keterampilan Motorik Kasar dan Kemampuan Kerjasama pada Anak Penyandang Tunagrahita Ringan - Hani Sri Juliani; Lukmannul Haqim Lubay; Wildan Alfia Nugroho; Gano Sumarno; Suherman Slamet (Jurnal Porkes, 2026)
This study aimed to determine the effectiveness of adaptive bowling games on gross motor skills and cooperation ability in children with mild intellectual disability. A single-subject research A-B-A design was used, involving four children aged 9-11 years at a special school in Bandung, Indonesia. The design comprised baseline (A1, 3 sessions), intervention (B, 6 sessions of adaptive bowling delivered twice weekly for 45-60 minutes), and withdrawal (A2, 3 sessions). Gross motor skills were measured using TGMD-3, while cooperation was assessed through a structured observation sheet. Data were analyzed using visual analysis and Percentage of Non-overlapping Data (PND). Results showed increased TGMD-3 scores in all subjects from baseline to intervention (29.3%-77.2%), with PND values indicating very effective to effective outcomes for three subjects. Cooperation scores improved in three subjects (PND up to 100%) but declined in one. Most gains were maintained during withdrawal. Adaptive bowling proved to be a feasible play-based strategy for simultaneously promoting motor and social development, while individualized adaptation remains necessary for children who respond differently to group-based intervention.